Sistem Pakar Fuzzy Untuk Optimasi Penggunaan Bandwidth Jaringan Komputer - Mustaziri, Mustaziri (Universitas Diponegoro, 2012)
The need for bandwidth availability today is very high along with the increase of infrastructural growth of internet network. Therefore, the presence of efficient, reliable, and economical service availability system is required. It can be achieved byperforming good and appropriate system planning. In providing efficient and reliable internet services, one of the supporting factors is the optimization of bandwidth using. To optimize the use of bandwidth, we use fuzzy expert system by Sugeno method. This fuzzy expert system use 3 input variables, such as lecture room, day, and t ime, with one output variable of the capacity of bandwidth used. Rule base being made based on the consultation with the expert to determine the rule base for fuzzy system input. The computation to determine the average error using the computation formula of MAPE (Means Absolute Percentage Error) which is the error median of absolute percentage. The data of the research results on the optimization of bandwidth using in fuzzy expert system with Sugeno method obtain from verification, that is by comparing actual data to prediction data with fuzzy system. The average error result is 6,5142 %.Keywords: Fuzzy Expert System; Optimization; Bandwidth